Learning through fun: board games cafes for undergraduate nursing students. (20th April 2023) - Simpson, Kate; Midgley, Katherine
Abstract : This article discusses the development, implementation and evaluation of clinical board games cafes in an undergraduate nurse education programme. Drawing on previous relevant literature about gaming approaches in education, the benefits and impact on student learning is presented. Thematic analysis of student feedback suggests that participation provided an opportunity to safely practise clinical scenarios and imbed concepts, as well as time to socialise to build support networks. Students also reported gaining confidence for their upcoming clinical placements. The benefits of a social opportunity timetabled during course teaching time was welcomed by students with commitments outside of the programme. The light-hearted cafe style environment can deliver a positive student experience and complement traditional teaching methods. Suggestions for future development include interdisciplinary sessions, development of games more specific to the mental health field and enabling students to get games out of the library for self-directed learning. Further evaluation of the impact of longer term learning through games is required.